THE CONCEPT OF POWER IN FANTASY LITERATURE: Martin, Rowling, Tolkien - Nadareishvili, Avtandil (Online Journal of Humanities ETAGTSU, 2021)
The article given below deals with the concept of power in 3 voluminous fantasy sagas. Its aim is to show how exactly the three well-known authors (G.R.R. Martin, J.K, Rowling and J.R.R.Tolkien) regard the phenomenon of power, find out how the personal qualities of a ruler influence his ability to rule, reveal the similarities and differences between the views of the three writers in this respect It is worth noting that the similarities greatly outnumber the differences, as the research has shown. The topic of power being one of the central themes of all three of them, comparative analysis has been chosen as the method of this particular research. There are plenty of works published concerning the three texts separately (they are acknowledged and duly cited where necessary), but the novelty of this article is that it analyzes and compares these novels in a parallel, simultaneous way.’ Full Text (PDF)